(untitled) (Web of Technology: Multidimensional Research Journal, 2023)
Big data and cloud computing are two of the most significant technological developments of the 21st century. They have transformed the way businesses and organizations store, process, and analyze data, leading to unprecedented levels of efficiency and innovation. In this article, we will explore the development trends of big data and cloud computing technologies, including their evolution, key features, benefits, challenges, and future prospects.